Analisis Semiotika Pesan Dakwah dalam Film Pendek Nilep - Vitria Dewi Rs; Muhammad Junaidi; Usrial Husein (Journal of Religion and Film, 2022)
This research is motivated by the development of increasingly sophisticated technology, making it easier to deliver dakwah messages through this technology. Currently, da'wah is not only carried out on the pulpit but has penetrated social media and cinema. This is what prompted the author to conduct research on the Nilep Short Movie produced by Ravacana Films. This study aims to determine how the meaning, connotations and myths contained in the Nilep Short Movie and to find out what da'wah messages are contained in the Nilep Short Movie. This research uses descriptive qualitative research methods. This research uses observation and documentation data collection techniques, by applying a data analysis technique, namely semiotic analysis using the Roland Barthes model. By using this semiotic analysis model of Roland Bartes, the writer can find out the meaning of denotation, connotation and myths, as well as the da'wah messages contained in the Nilep Short Movie. The result, the writer found that the object of semiotic analysis research are image/visual, shot type and sound/audio. The writer also finds denotative meanings, connotative meanings and myths contained in the Nilep Short Movie. The author also found several da'wah messages in the short movie, namely please help, be grateful, empathize, do not repay evil for evil as well, reject munkar, do not steal, hasten good deeds, check the truth of information, say and answer greetings, and ask for sorry and forgive. Finally, the writer recommends readers to watch and retrieve the da'wah messages contained in the Nilep Short Movie.